Preoperative versus postoperative radiotherapy for localized soft tissue sarcoma treated with curative intent in a French tertiary center “SARCLOC” - Maxime Noeuveglise; Williams Tessier; Maël Barthoulot; Gauthier Decanter; Antoine Cayeux; Helene Marin; Pauline Lemoine-Gobert; Estelle Aymes; Sophie Taieb; Cindy Fayard; Juliette Beaujot; Yves-Marie Robin; et al. (BMC Cancer)
Abstract Background Soft tissue sarcomas of the extremities (E-STS) are rare and heterogeneous. Treatment combines surgery with preoperative or postoperative radiotherapy (RT) for deep, large, or high-grade tumors. We evaluate the effectiveness and toxicity in E-STS patients treated at our institution from 2015 to 2021. Materials and methods This retrospective, single-center study, compared clinical and therapeutic characteristics, toxicities, and surgical complications by radiotherapy type. Local recurrence-free survival (LRFS), overall survival (OS), and recurrence-free survival (RFS) were estimated using the Kaplan–Meier method. Results We included 158 patients; 124 (78%) received preoperative RT. The two groups (preoperative RT vs. postoperative RT) differed significantly in terms of median tumor size (111 vs. 67.5 mm, p < 0.01), perivascular involvement (51% vs. 29%, p = 0.03), and bone contact (32% vs. 12%, p = 0.02), but not in grade (grade 2 or 3: 65% vs. 74%, p = 0.72). Median follow-up was 2.9 vs. 5.1 years. Two-year LRFS was 82% [95%CI: 74–88] for both groups; OS was 87% [95%CI: 80–92] vs. 88% [95%CI: 71–95]; and RFS was 72% [95%CI: 63–79] vs. 70% [95%CI: 52–83]. Postoperative complications were 53% vs. 35%, with wound disruption at 39% vs. 15% and infections at 29% vs. 6%. Grade 2 or higher dermatitis was 16% vs. 29%, and RT discontinuation rates were 4% vs. 12% for the two groups, respectively. Conclusion Despite poorer prognostic factors in the preoperative RT group, LRFS and OS were comparable to those in the postoperative RT group. Postoperative complications were more frequent with preoperative RT, and treatment discontinuation was more common postoperatively.